ChemInform Abstract: Data Sampling in Multidimensional NMR: Fundamentals and Strategies. Issue 3 (22nd January 2013) - Maciejewski, Mark W.; Mobli, Mehdi; Schuyler, Adam D.; Stern, Alan S.; Hoch, Jeffrey C.
Abstract Review: 46 refs.